Comparison Of Protein Expression Between Breast And Colorectal Cancers - Lee , Hui Hua (2012)
Up to date, cancer remains a major health problem across the globe. Breast cancer is the most common cancer among women while colorectal cancer is the third most common cancer in both genders worldwide. In view of breast and colorectal cancer being among the most common types of cancer in Malaysia, we aimed to identify common biomarkers that can be used in the diagnosis or treatment of the cancers. This aim is accomplished by studying the protein expression profiles of breast and colorectal cancers tissues in comparison with their respective normal tissues.